Temperature dependence of cracking resistance of 15KhSND steel and special features of its fracture. Report 2 - Gol'dshtein, R.V.; Ovsyannikov, B.M.; Surovova, V.N. (Проблемы прочности, 1985)
In the previous article, we presented the results of investigations into the temperature dependence of the cracking resistance of 15KhSND steel in the temperature range --80° to +20° obtained using the methods which make it possible to produce specimens of small thicknesses. We shall now examine the special features of failure of this material which make it possible to propose a model of the process explaining the observed effects. It should be mentioned that although quantitative evaluation was carried out using the experimental data for 15KhSND steel, the model may also be used in analysis of identical effects in other widely used low-alloy steels.